The DPY30-H3K4me3 Axis-Mediated PD-L1 Expression in Melanoma - Zhang Z; Han Y; Sun Q; Wang Y; Sun L (Dove Medical Press, 2022)
Zhichun Zhang,1 Yixuan Han,2 Qiuyue Sun,1 Yipeng Wang,3 Lichao Sun4 1Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 2Department of Rheumatology and Immunology, Affiliated Kailuan General Hospital of North China University of Science and Technology, Tangshan, People's Republic of China; 3Department of Breast Surgery, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of China; 4State Key Laboratory of Molecular Oncology, National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences, Peking Union Medical College, Beijing, People's Republic of ChinaCorrespondence: Lichao Sun; Yipeng Wang, National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100021, People's Republic of China, Tel/Fax +86 10-67781331, Email sunlichao@cicams.ac.cn; yidoctor99@126.comBackground: DPY30 is a common subunit of the human SET1/MLL complex and is an essential protein required for the activity of SET1/MLL methyltransferase. DPY30 regulates the histone H3K4 modification, and dysfunction of DPY30 might contribute to the regulation of cancer immune evasion. However, the functions and regulation of DPY30 in the expression of programmed cell death ligand 1 (PD-L1) is still not completely explored.Methods: Various online databases were used for data processing and visualization, including UALCAN, Oncomine, cBioPortal, SangerBox, TISIDB, TIMER, and GEPIA databases. The expression of DPY30 and PD-L1 in melanoma tissues were evaluated by IHC. Chromatin Immunoprecipitation (ChIP), RT-PCR and flow cytometry were used to elucidate the underlying molecular mechanism of PD-L1 expression regulation and its function.Results: The mRNA level of DPY30 in melanoma was higher than in normal tissues. The expression of DPY30 was positively associated with TMB, neoantigens and PD-L1 expression. Furthermore, DPY30 expression showed significant positive correlations with immune suppressor cells and ICP genes involved in T-cell exhaustion. IHC showed that the positive rates of DPY30 and PD-L1 in melanoma tissues were 62% and 58%, respectively. Correlation analysis revealed that DPY30 over-expression was positively associated with PD-L1 expression. Silencing of DPY30 by specific siRNA significantly inhibited PD-L1 expression. ChIP analysis revealed that H3K4me3 levels were enriched in the proximal PD-L1 promoter region in tumor cells. Inhibition of DPY30 still suppressed the PD-L1 level in IFN-γ treated MMAC-SF cells. Furthermore, the apoptosis of PD1+ T-cells in co-culture with MMAC-SF cells by knockdown of DPY30 were markedly reduced.Conclusion: This study shows the roles of DPY30 in regulating the cancer immune evasion in melanoma. Targeting the DPY30-H3K4me3 axis might be an alternative approach to enhance the efficacy of checkpoint immunotherapy.Keywords: DPY-30, H3K4me3, PD-L1, melanoma, immunotherapy